JMCR 2021
DOI: 10.7176/jmcr/78-04
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Moderating Role of Social Support in Online Shopping Intentions

Abstract: Relationship building plays a crucial role in business success because of the saturated nature of the market. Thus, there has been stronger competition because many businesses offer similar products for sale on an online shopping platform. This has given online consumers a wide range of alternatives when shopping online. This present study aimed to investigate the influence of relationship quality on purchase intention among Ghanaian consumers in an online shopping platform while moderated by social support. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Hence, these findings supported the idea that donors who considered making a donation were more likely to look for the input and advice of other members among the crowdfunding community and to develop a sense of confidence in the platform. A number of recent studies [39,47,48] have shown that the availability of information may influence donors' purchase decisions or intentions. Therefore, this study argued that informational support has an impact on donors' willingness to donate.…”
Section: Social Support's Impact On Trust and Intention To Donatementioning
confidence: 99%
“…Hence, these findings supported the idea that donors who considered making a donation were more likely to look for the input and advice of other members among the crowdfunding community and to develop a sense of confidence in the platform. A number of recent studies [39,47,48] have shown that the availability of information may influence donors' purchase decisions or intentions. Therefore, this study argued that informational support has an impact on donors' willingness to donate.…”
Section: Social Support's Impact On Trust and Intention To Donatementioning
confidence: 99%